Improved Osteogenesis by Mineralization Combined With Double-Crosslinked Hydrogel Coating for Proliferation and Differentiation of Mesenchymal Stem Cells - Ma, Yiqun; You, Yuwang; Cao, Lu; Liang, Bing; Tian, Bo; Dong, Jian; Lin, Hong (Frontiers in Bioengineering and Biotechnology, 2021)
In consideration of improving the interface problems of poly-L-lactic acid (PLLA) that hindered biomedical use, surface coatings have been explored as an appealing strategy in establishing a multi-functional coating for osteogenesis. Though the layer-by-layer (LBL) coating developed, a few studies have applied double-crosslinked hydrogels in this technique. In this research, we established a bilayer coating with double-crosslinked hydrogels [alginate–gelatin methacrylate (GelMA)] containing bone morphogenic protein (BMP)-2 [alginate-GelMA/hydroxyapatite (HA)/BMP-2], which displayed great biocompatibility and osteogenesis. The characterization of the coating showed improved properties and enhanced wettability of the native PLLA. To evaluate the biosafety and inductive ability of osteogenesis, the behavior (viability, adherence, and proliferation) and morphology of human bone mesenchymal stem cells (hBMSCs) on the bilayer coatings were tested by multiple exams. The satisfactory function of osteogenesis was verified in bilayer coatings. We found the best ratios between GelMA and alginate for biological applications. The Alg70-Gel30 and Alg50-Gel50 groups facilitated the osteogenic transformation of hBMSCs. In brief, alginate-GelMA/HA/BMP-2 could increase the hBMSCs’ early transformation of osteoblast lineage and promote the osteogenesis of bone defect, especially the outer hydrogel layer such as Alg70-Gel30 and Alg50-Gel50.